Multimedia vs concrete model: Review of studies employing the tools in chemistry teaching - Rooserina Kusumaningdyah; Habiddin Habiddin; Yudhi Utomo (Universitas Negeri Malang, 2021)
This paper describes previous studies regarding the use of multimedia or virtual model and concrete model to improve students’ understanding of chemistry. Thirty-three relevant papers in various topics, including stereochemistry, symmetry, chemical bonding, law conservation of matter, and others, were found and discussed. In particular, relevant studies in stereochemistry teaching is also discussed. REFERENCESAnggriawan, B. (2017). Pengaruh Pembelajaran Penemuan Terbimbing Berbantuan Multimedia terhadap Pemahaman Materi Simetri Mahasiswa dengan Kemampuan Spasial yang Berbeda. Universitas Negeri Malang.Beauchamp, P. S. (1984). “Absolutely” Simple Stereochemistry. Journal of Chemical Education, 61(8), 666. https://doi.org/10.1021/ed061p666Boukhechem, M.-S., Dumon, A., & Zouikri, M. (2011). The Acquisition of Stereochemical Knowledge by Algerian Students Intending to Teach Physical Sciences. Chemical Education Research and Practise, 12(3), 331–343. https://doi.org/10.1039/C1RP90040DChen, D., Chen, X., & Gao, W. (2013). The Application and Perspective of Multimedia Technology in Chemistry Experimental Instruction in China. Creative Education, 04(04), 241–247. https://doi.org/10.4236/ce.2013.44035Chen, D.-W., & Catrambone, R. (2014). Effects of Multimedia Interactivity on Spatial Task Learning Outcomes. Proceedings of the Human Factors and Ergonomics Society Annual Meeting, 58(1), 1356–1360. https://doi.org/10.1177/1541931214581283da Silva Júnior, J. N., Sousa Lima, M. A., Xerez Moreira, J. V., Oliveira Alexandre, F. S., de Almeida, D. M., de Oliveira, M. da C. F., & Melo Leite Junior, A. J. (2017). Stereogame: An Interactive Computer Game That Engages Students in Reviewing Stereochemistry Concepts. Journal of Chemical Education, 94(2), 248–250. https://doi.org/10.1021/acs.jchemed.6b00475Dayame, A. M. (2019). The Effects of Manipulative and Visual Models in Conceptualizing Fractions. International Journal of Advanced Research and Publications, 3(8), 80–85.Dori, Y. J., & Barak, M. (2001). Virtual and Physical Molecular Modeling: Fostering Model Perception and Spatial Understanding. Educational Technology & Society, 4(1), 61–74.Hakim, M. F., Maksum, A. H., Saragih, Y., & Hasanah, C. S. (2020). Analysis on the implementation of virtual versus reality laboratory. J-PEK (Jurnal Pembelajaran Kimia), 5(2), 59–65. https://doi.org/10.17977/UM026V5I22020P059Harrold, M. W. (1995). Computer-Based Exercises to Supplement the Teaching of Stereochemical Aspects of Drug Action1,2. American Journal of Pharmaceutical Education, 59, 20–26.Kirk, J. (2015). Using Manipulatives in The Chemisty Classroom as a Tool to Increase The Understanding and Knowledge of The Law of Conversation of Matter. St. John Fisher College: Fisher Digital Publications:Knowles, T. H. (2017). Using Eye-Tracking and Molecular Modelling to Explore Students’ Strategies for Solving Organic Stereochemical Problems. University of Northern Colorado.Koutalas, V. G., Antonoglou, L. D., Charistos, N. D., & Sigalas, M. P. (2014). Investigation of Students’ Ability to Transform and Translate 2D Molecular Diagrammatic Representations and its Relationship to Spatial Ability and Prior Chemistry Knowledge. Procedia - Social and Behavioral Sciences, 152, 698–703. https://doi.org/10.1016/j.sbspro.2014.09.265Lou, S.-J., & Lin, H.-C. (2012). Improving the Effectiveness of Organic Chemistry Experiments through Multimedia Teaching Materials for Junior High School Students. The Turkish Online Journal of Educational Technology, 11(2), 135–141.Muchson, M., Munzil, M., Winarni, B. E., & Agusningtyas, D. (2019). Pengembangan virtual lab berbasis android pada materi asam basa untuk siswa SMA. J-PEK (Jurnal Pembelajaran Kimia), 4(1), 51–65. https://doi.org/10.17977/UM026V4I12019P051O’Brien, M. (2016). Creating 3-Dimensional Molecular Models to Help Students Visualize Stereoselective Reaction Pathways. Journal of Chemical Education, 93(9), 1663–1666. https://doi.org/10.1021/acs.jchemed.6b00250Olimpo, J. T., Kumi, B. C., Wroblewski, R., & Dixon, B. L. (2015). Examining The Relationship Between 2D Diagrammatic Conventions and Students’ Success on Representational Translation Tasks in Organic Chemistry. Chemistry Education Research and Practice, 16(1), 143–153. https://doi.org/10.1039/C4RP00169AOlkun, S. (2003). Comparing Computer versus Concrete Manipulatives in Learning 2D Geometry. Journal of Computers in Mathematics and Science Teaching, 22(1), 43–56. https://doi.org/10.1501/0000984Sentongo, J., Kyakulaga, R., & Kibirige, I. (2013). The Effect of Using Computer Simulations in Teaching Chemical Bonding: Experiences with Ugandan Learners. International Journal of Education Science, 5(4), 433–441.Sevi̇Nç, B. (2010). The Effect Of Computer Based Instruction Enhanced With Concept Maps On Students’ Understanding Of Stereochemistry. International Conference on New Trends in Education and Their Implications, 301–306.Stieff, M., Bateman, R. C., & Uttal, D. H. (2005). Teaching and Learning with Three-dimensional Representations. In J. K. Gilbert (Ed.), Visualization in Science Education (pp. 93–120). Springer Netherlands. https://doi.org/10.1007/1-4020-3613-2_7Stieff, M., Scopelitis, S., Lira, M. E., & Desutter, D. (2016). Improving Representational Competence with Concrete Models. Science Education, 100(2), 344–363. https://doi.org/10.1002/sce.21203Stull, A. T., Barrett, T., & Hegarty, M. (2013). Usability of Concrete and Virtual Models in Chemistry Instruction. Computers in Human Behavior, 29(6), 2546–2556. https://doi.org/10.1016/j.chb.2013.06.012Stull, A. T., Hegarty, M., Dixon, B., & Stieff, M. (2012). Representational Translation With Concrete Models in Organic Chemistry. Cognition and Instruction, 30(4), 404–434. https://doi.org/10.1080/07370008.2012.719956Thayban, T., Habiddin, H., & Utomo, Y. (2020). Concrete Model VS Virtual Model: Roles and Implications in Chemistry Learning. J-PEK (Jurnal Pembelajaran Kimia), 5(2), 90–107. https://doi.org/10.17977/UM026V5I22020P090Thayban, T., Habiddin, H., Utomo, Y., & Muarifin, M. (2021). Understanding of Symmetry: Measuring the Contribution of Virtual and Concrete Models for Students with Different Spatial Abilities. Acta Chimica Slovenica, 68(3). https://doi.org/10.17344/acsi.2021.6836